2020
DOI: 10.1088/1755-1315/462/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fiber fraction, physical and chemical properties of coffee flour (Coffea sp.) as functional foodstuff for diabetes mellitus patient

Abstract: Coffee pulp is solid waste from coffee processing, but unfortunately, it has not been utilized optimally, particularly for foods. Objective of the research was to study characterization of fiber fraction, physical and chemical properties of coffee flour as functional dietary material, which is rich in fiber to reduce blood glucose level for diabetes mellitus patients. The research used Arabica and Robusta coffee pulps. Results of the research showed that characterization of fiber fraction for Arabica has solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…It is vital since high dietary fibre intake helps diminish the chances of heart disease and obesity while lowering high blood pressure, maintaining ideal sugar content in the blood, and preventing colon cancer. Furthermore, in the case of cardiovascular conditions (coronary heart), fibre binds bile acids to reduce cholesterol in the blood (Damat et al, 2019;Elba et al 2017;Mindarti et al 2020;Wahyani and Rahmawati 2021). Furthermore, as insoluble dietary fibre, lignin thickens food mass in the digestive system, and it is adequate to prevent digestive ailments such as hemorrhoids, diverticulosis, and colon cancer (Damat et al, 2019;Mindarti et al 2020).…”
Section: Lignin Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is vital since high dietary fibre intake helps diminish the chances of heart disease and obesity while lowering high blood pressure, maintaining ideal sugar content in the blood, and preventing colon cancer. Furthermore, in the case of cardiovascular conditions (coronary heart), fibre binds bile acids to reduce cholesterol in the blood (Damat et al, 2019;Elba et al 2017;Mindarti et al 2020;Wahyani and Rahmawati 2021). Furthermore, as insoluble dietary fibre, lignin thickens food mass in the digestive system, and it is adequate to prevent digestive ailments such as hemorrhoids, diverticulosis, and colon cancer (Damat et al, 2019;Mindarti et al 2020).…”
Section: Lignin Contentmentioning
confidence: 99%
“…Furthermore, in the case of cardiovascular conditions (coronary heart), fibre binds bile acids to reduce cholesterol in the blood (Damat et al, 2019;Elba et al 2017;Mindarti et al 2020;Wahyani and Rahmawati 2021). Furthermore, as insoluble dietary fibre, lignin thickens food mass in the digestive system, and it is adequate to prevent digestive ailments such as hemorrhoids, diverticulosis, and colon cancer (Damat et al, 2019;Mindarti et al 2020). Astawan and Wresdiyati (2004), Dreher (2018), Fung-Jou et al (1998, Harbone (1996), Huang et al (2010), Kritchevsky and Bonfield (2012), Soliman (2019), Suarni and Firmansyah (2007), Veronese et al (2018), andYahia et al (2019) were therefore in unison that lignin is an antioxidant compound.…”
Section: Lignin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee processing solid waste (pulps and husks) further increases the added value when processed as additional food ingredients. Setyobudi et al [28], Mindarti, et al [29] suggested that coffee husks and pulps be transformed into functional food, namely coffee cherry flour (CCF). Damat et al [30] stated that CCF has a positive impact because it increases the dietary fiber and antioxidant activity in cookies made from gluten-free ingredients.…”
Section: Development -Waste Utilizationmentioning
confidence: 99%
“…Andrew Fedak and Dan Belliveau proposed to turn CP and CH into Coffee Cherry Flour (CCF) (Cheatham, 2019;WIPO-PCT, 2014). Damat et al (2019), Elba et al (2017), Mindarti et al (2020), Moreno et al, 2019, andRosas-Sánchez et al (2021) have discussed CCF's positive impacts on its fibre content, while Setyobudi et al (2019 and 2021a) advised CCF to be an iron (Fe) source. The latter, after reviewing a considerable amount of data, discovered that CP and CH contained Fe between (4.3 to 50) mg 100 g -1 (Anna et al, 2019;Avinash et al, 2017;Elias, 1979;Hermosa et al, 2014;Iriondo-DeHond et al 2020;Kayhanian and Tchobanoglous , 2016;Marín-Tello et al, 2020, Setyobudi et al, 2018Wich, 2015;Zupancic and Grilc, 2012).…”
Section: Introductionmentioning
confidence: 99%